PENGARUH VARIASI SUHU SIKLUS THERMAL TERHADAP KEKUATAN BENDING KOMPOSIT UNSATURATED POLYESTER SERAT KELAPA - SEMBADA, IQBAL VARIAN; Hermawan, Yuni; listyadi S, Digdo; Sholahudin, Imam; Kristianta, FX (Jurusan Teknik Mesin, 2024)
Composite is one of the materials used in engineering field. This is because composites have strong properties, light weight, corrosion resistance, economical and so on. One of coconut fiber composite composite. Coco fiber in Indonesia is still not utilized to the maximum to increase its economic value. One application of coconut fiber composite usage is for wood replacement wall. This study aims to determine the effect of repeated thermal load on the bending strength of the composite. In this research the material used is coconut fiber coir random orientation direction as reinforced and unsaturated polyester as matrix with fiber volume fraction 5%. The production method used is press hand lay up. Temperature variations are 30oC, 50oC, 70oC, and 90oC with 10 repetitions. Bending test is done with ASTM D790 standard reference. The result of this research shows the highest bending strength in composite with thermal temperature of 30o C equal to 39,68 MPa. While the lowest bending strength occurred at 90°C thermal temperature of 24.60 MPa. From result of research indicate that unsaturated polyester when given heat load continuously will decrease bending strength because debonding failure in matrix.